Pengembangan Modul Fisika Kelas VII SMP/MTs Berbasis Interelasi Al-Qur’an Dan Sains Pada Materi Ajar Kalor - Nurhafizah Nurhafizah; Zainuddin Zainuddin; Syubhan An'nur (Berkala Ilmiah Pendidikan Fisika, 2015)
The low of student learning outcomes in learning physics because the response to science learning still low and lack of availability of physics module SMP/MTs which connect Qur’an with science. It is necessary for research that aims to determine the feasibility of physics module class VII SMP/MTs based interrelation of the Qur'an and science. The special purpose, namely: (1) the validity of the module, (2) implemented of RPP, (3) student learning outcomes, and (4) student’s response. The development of physics module refers to the ADDIE model, namely: (1) analysis, (2) design, (3) development, (4) implementation, and (5) evaluation. Subjects were 33 students of class VII B SMP State 17 Banjarmasin academic year 2013/2014 as a test grade. Data collection technique used instrument validation module, observations, test results of students’ learning and questionnaire responses. The results of research and development showed that: (1) the validity of modules on validation material is excellent category, validation media is excellent category, and validation interrelation is good category, (2) implemented of RPP in the excellent category, (3) student learning outcomes at the first meeting in quite effective category, second meeting in quite effective category, and third meeting in less effective category, (4) students’ response in good category. We concluded that the feasibility of the physics module class VII SMP/MTs based interrelation of the Qur'an and science in the worthy category.